Public attention to environmental issues and stock market returns - Imane El Ouadghiri; Khaled Guesmi; Jonathan Peillex; Andreas Ziegler (Philipps-University Marburg, School of Business and Economics, 2019)
This paper empirically examines the effect of public attention to climate change and pollution on the weekly returns on US sustainability stock indices (i.e. the DJSI US and the FTSE4Good USA Index) in comparison to their conventional counterparts (i.e. the S&P 500 Index and the FTSE USA). In addition to unexpected global climate-related natural weather disasters, we consider two complementary measures of public attention to these environmental issues: (i) US media attention to climate change and pollution and (ii) the US Google Search Volume Index for these two keywords. Robust to several sensitivity analyses, our econometric analysis for the period from 2004 to 2018 reveals that public attention to environmental issues has a significantly positive (negative) effect on the returns on US sustainability (conventional) stock indices. A possible explanation of this result is that high public attention to environmental issues may drive traditionally sustainable investors, neo-sustainable, and opportunistic self-interested investors to favor stocks of sustainable firms. The insights from our empirical study are important for private and institutional investors, managers of firms, and public policy.
Keywords: Q51; G14; Q53; Q54; 330; Public attention; environmental issues; stock returns; sustainability stock indices; asset pricing models